Müzik Dersinde Zihin Haritalama Tekniği Kullanımının Öğrencilerin Müzik Dersi Başarılarına ve Zihin Haritalama Tekniğine Yönelik - (:unkn) unknown (My University, 2017)
Bu araştırmanın amacı, müzik derslerinde kullanılan zihin haritalama tekniğinin, öğrencinin başarısına ve zihin haritalama tekniğine yönelik tutumlarına ne ölçüde etkisi olduğunu belirlemektir. Araştırma 2014-2015 Eğitim-Öğretim Yılı'nda, İstanbul ilinin Ümraniye ilçesinde bulunan Özel Ümraniye Bahçeşehir İlkokulu 3. Sınıfta öğrenim gören toplam 37 öğrenci ile yapılmıştır. Araştırmada bir deney ve bir kontrol grubu kullanılmıştır. Deney grubuna; zihin haritalama tekniğinin uygulanması aşamasında, "Bildiğimiz Çalgılar" konusuna ilişkin birer saatlik altı ders planı hazırlanmış, planla ilgili öğrenciler bilgilendirilmiş ve toplam altı saatte kazanımlar öğrencilere verilmeye çalışılmıştır. Kontrol grubunda ise, geleneksel yöntem uygulanmıştır. Araştırmada sayısal verilerin elde edilmesinde Mann Whitney-U Testi ile Wilcoxon Testi yapılmıştır. Araştırma sonucunda; deney ve kontrol grubunun homojen bir yapıya sahip olduğu, araştırmaya katılan kişilerin son test puanlarında ise sadece deney gurubu başarı puanlarında anlamlı bir fark bulunmuştur.

The aim of this research is to determine the effect of the mind mapping technique used in music lesson on student's achievements and on their attitudes towards the mind mapping technique. Research was conducted with a total of thirty-seven students studying in third grade in 2014-2015 academic years in Ümraniye District of Istanbul Private Ümraniye/ Bahçeşehir Elementary School. An experimental and a control group were used in the research. During the implementation of mind mapping techniques in the experimental group, a six-hour lesson plan was prepared on the "Familiar Instruments" subject; then students were informed about the proposed plan and expected achievements from them. In the control group which traditional method was applied, teacher created the lesson plan before entering the course. With regard to the experiment group, totally six hours of course plan comprised of six individual 1-hour sessions was prepared on the subject of "Familiar Music Instruments"; students were notified about this plan; and acquisitions were tried to be given to the students during application of mind map technique. On the other hand, the conventional method was applied with the control group. Mann Whitney-U Test and Wilcoxon Test were conducted during collection of numerical data. As a result of the study, it was determined that experiment and control group were displaying homogenous structure; and that a significant difference was determined only with the post-test scores of the participants from the experiment group
The Effect of Mind Mapping Technique on Students' Achievements in Music Lesson and on Their Attitudes towards the Mind Mapping Technique *
Keywords: Eğitim, Eğitim Araştırmaları; Eğitim, Özel; Müzik